Nutrihealth indicator / Nur Bashirouh Attaullah ... [et al.] - Attaullah, Nur Bashirouh; Azmi, Nur Nadiah; Mohamad Azenal, Siti Nur Farhana; Said, Dayana; MD Rafi, Nurul Farina (2018)
Nutri Health Indicator is a portable food indicator that detects and measures various elements in our daily meal such as calorie, sugar, salt and fat. This device combines many indicators that are currently used in the industry. Unlike all the bulky indicators used in hospitals and laboratories, this device uses the same mechanism, science and concept; however Nutri Health comes in a portable size. This device is also able to store information on nutrients, making it easy for customers to track their daily, weekly, and even monthly intake of nutrients.